PERANCANGAN KEMASAN GULA AREN ARTO MORO DAERAH PADANG KUBIN - UMARO RAHMAN, Dr. Budiwirman, M.Pd., Dra. Zubaidah, M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2019)
Arto Moro in Padang Kubin, Kabupaten 50 Kota is a household mice industry engaged in productions of palm sugar. The marketing of Arto Moro palm sugar products already covers most of the traditioanal markets in Kabupaten 50 Kota and Payakumbuh. Arto Moro wats to expand its product to modern shopping areas. However, packaging of palm sugar products still traditionally using dried leaves. Therefore, Arto Moro needs a package to support sales in the modern market. The purpose of this design is produce an attractive packaging, informative, and communicative so that can support the sale of products to modern market.The methods used in this packaging design is SWOT analysis method (Stregth, Weakness, Opportunity, Treatment) to find the design solution. The palm sugar packaging Arto Moro will be designed with a modern concept, elegant, simple but stil shows the traditional impression.This design produces a distinctive packaging that makes it easy for consumers to recognise. Leter packaging will also be supported by other media such as poster, x-banners, pron, invoices, business cards, stikers and paper bags as a media to support Arto Moro’s business activities.Key words: Design, Packaging, Arto Moro